Interleukin inhibitors and the associated risk of candidiasis - Khan, Sabir; Bilal, Hazrat; Khan, Muhammad Nadeem; Fang, Wenjie; Chang, Wenqiang; Yin, Bin; Song, Ning-jing; Liu, Zhongrong; Zhang, Dongxing; Yao, Fen; Wang, Xun; Wang, Qian; et al. (Frontiers in Immunology, 2024)
Interleukins (ILs) are vital in regulating the immune system, enabling to combat fungal diseases like candidiasis effectively. Their inhibition may cause enhanced susceptibility to infection. IL inhibitors have been employed to control autoimmune diseases and inhibitors of IL-17 and IL-23, for example, have been associated with an elevated risk of Candida infection. Thus, applying IL inhibitors might impact an individual’s susceptibility to Candida infections. Variations in the severity of Candida infections have been observed between individuals with different IL inhibitors, necessitating careful consideration of their specific risk profiles. IL-1 inhibitors (anakinra, canakinumab, and rilonacept), IL-2 inhibitors (daclizumab, and basiliximab), and IL-4 inhibitors (dupilumab) have rarely been associated with Candida infection. In contrast, tocilizumab, an inhibitor of IL-6, has demonstrated an elevated risk in the context of coronavirus disease 2019 (COVID-19) treatment, as evidenced by a 6.9% prevalence of candidemia among patients using the drug. Furthermore, the incidence of Candida infections appeared to be higher in patients exposed to IL-17 inhibitors than in those exposed to IL-23 inhibitors. Therefore, healthcare practitioners must maintain awareness of the risk of candidiasis associated with using of IL inhibitors before prescribing them. Future prospective studies need to exhaustively investigate candidiasis and its associated risk factors in patients receiving IL inhibitors. Implementing enduring surveillance methods is crucial to ensure IL inhibitors safe and efficient utilization of in clinical settings.